Interaction of a mesoscale low and diffused tropical depression during south Asian summer monsoon - RASUL, GHULAM; CHAUDHRY, QAMARUZZAMAN; ZENG, QINGCUN; ZHAO, SIXIONG; SHOUTING, GAO (MAUSAM, 2008)
This paper presents the results of a diagnostic study of a typical case in south Asian summer monsoon when a meso-scale low in a desert climate interacted with a diffused tropical depression originated over the Bay of Bengal. Surface and NCEP reanalysis data supported by satellite and radar images were incorporated in diagnosis. The relationship between heavy precipitation process and large-scale circulations such as westerly jet, low level jet, convergence, vorticity and water vapor transport were investigated to further understand the mechanism of this peculiar interaction. It has been found that the meso-scale low developed as a result of cold air advection aloft from northern latitudes and strong convection over the region of humidity convergence, i.e., Rajasthan (India) on 24th July 2003. On the same day, a low formed on the Bay of Bengal which further developed into monsoon depression. It moved westward from the Bay towards the meso-scale low over southwest India. Meso-scale low remained more or less stationery for two days gaining intensity and then moved relatively with slower speed in southwestward direction. Both the systems yielded moderate to heavy rain in areas under their influence. Interaction resulted into huge accentuation with an abrupt increase in intensity.